Sanata Dharma menemukan jalannya - Suwarno, P.J. (Yogyakarta : Universitas Sanata Dharma, 1998)
History of Sanata Dharma, an Indonesian Catholic universiti Yogyakarta
Includes bibliographical references
Keywords: Universitas Sanata Dharma -- History